Evolution of mobile handset feature dependences - Alexandr Vesselkova; Antti Riikonena; Hämmäinena; Heikki (International Telecommunications Society (ITS), 2015)
Within 20 years, the mobile handset has evolved from the basic phone merely capable of voice calling to the advanced smartphone, which combines voice communication with multiple other functionalities. Mobile handset components, or features, along with evolving communications infrastructure, enable a smartphone to run numerous mobile applications and services. Therefore, mobile operators, application developers, service providers, and regulators are increasingly interested in the information on mobile handset feature diffusion for making effective managerial and investment decisions. This paper quantitatively studies dependences between mobile handset features, which need to be analyzed for understanding and estimating future feature diffusion. The study is based on an extensive dataset on mobile handset sales in Finland and utilizes a method of hierarchical clustering for identifying the sets of dependent features. The results show that the features became increasingly dependent in 2008-2014. Although the nature of feature dependences differs, on a general level, they arise from mobile handset design decisions made by the device producers. The factors influencing these design decisions and consequently feature dependences can be divided in four main groups: technology, demand, product strategy, standardization and regulatory factors.
Keywords: 330; handset feature; feature dependence; feature diffusion; dissemination; handset evolution